2019
DOI: 10.1038/s41598-019-49006-2
|View full text |Cite
|
Sign up to set email alerts
|

Critical Transitions in Intensive Care Units: A Sepsis Case Study

Abstract: The progression of complex human diseases is associated with critical transitions across dynamical regimes. These transitions often spawn early-warning signals and provide insights into the underlying disease-driving mechanisms. In this paper, we propose a computational method based on surprise loss (SL) to discover data-driven indicators of such transitions in a multivariate time series dataset of septic shock and non-sepsis patient cohorts (MIMIC-III database). The core idea of SL is to train a mathematical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
0
14
0
2
Order By: Relevance
“…In neuroscience, Bashan et al (2012) demonstrated that several integrated physiological systems play part in topological transition in sleep stages. Ghalati et al (2019) used the Surprise Loss (SL) approach to characterize the critical transition that occurs before a septic shock. Dakos et al (2008) illustrated the critical slowing down that precedes tipping points in climate transitions, using a time-series autocorrelation approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In neuroscience, Bashan et al (2012) demonstrated that several integrated physiological systems play part in topological transition in sleep stages. Ghalati et al (2019) used the Surprise Loss (SL) approach to characterize the critical transition that occurs before a septic shock. Dakos et al (2008) illustrated the critical slowing down that precedes tipping points in climate transitions, using a time-series autocorrelation approach.…”
Section: Discussionmentioning
confidence: 99%
“…While the structure of this network is far from being elucidated and many nodes are still unidentified, it may nonetheless be possible to infer much about the network via sampling of small subsets of nodes (i.e., molecules), due to the emergent properties of the network as a whole that lend coherence to its state and dynamics (Cohen, 2016;Cohen et al, 2021). This approach can be linked to a more general area of complex systems theory that has recently gained substantial attention: critical transitions (Dakos et al, 2008(Dakos et al, , 2012Scheffer et al, 2009;Bashan et al, 2012;Ghalati et al, 2019). In complex systems, system dynamics such as a change in variability may provide early warning signs (EWSs) of impending state changes known as critical transitions (e.g., ecological collapse, financial crises, and shifts in climate regime).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In einer Studie von Ghalet et al wurde die sog. "Surprise Loss"-Methode angewendet, um klinische Veränderungen an Sepsispatienten zu identifizieren und zu charakterisieren [7]. Hierbei werden minimale Instabilitäten in großen Datensätzen identifiziert, in diesem Fall Veränderungen von Parametern, die auf eine Progression einer Organdysfunktion bei einer Sepsis ("Transition der kritischen Erkrankung") hinweisen.…”
Section: Merkeunclassified
“…As a consequence, clipping or padding techniques are applied, altering the underlying temporal structure. In recent years, studies on such data have seen an increasing popularity in a wide range of fields, from functional magnetic resonance imaging (fMRI) (Van Den Heuvel and Pol, 2010 ; Azarmi et al, 2019 ; Yan et al, 2019 ) to time series exploration for critical transition prediction in clinical scenarios (Cuesta-Frau et al, 2019 ; Ghalati et al, 2019 ). The common goal of this type of research is to develop models and algorithms capable of reaching the highest possible classification and prediction performances, for diagnostic and real-time applications, while unveiling underlying information about a system.…”
Section: Introductionmentioning
confidence: 99%